(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
Research of interaction of Hoechst 33258 with DNA, binding through a minor groove of DNA, by spectroscopic (fluorescent and absorption) methods is carried out. It is revealed, that this ligand with DNA binds by two modes – strong and weak. The strong type of interaction Hoechst 33258 with DNA is detected by both fluorescent and absorption methods, while the weak type is observed only by the absorption method. On the basis of the analysis of the spectroscopic data values of parameters of linkage - K and n are calculated.